The variability of atmospheric circulation over Poland in the years 1950–2021 - Piotrowski, Piotr (Acta Geographica Lodziensia, 2023)
The Jenkinson and Collison method, originally used to automate the weather type classification developed by Lamb for the British Isles, was used to develop a catalog of atmospheric circulation types in Poland. Sixteen directional atmospheric circulation types (ACTs) from this method were used for the characterization of circulation conditions in Poland. They were determined based on the direction of the geostrophic wind and the distinction between cyclonic and anticyclonic circulation based on shear vorticity. Both circulation indices were calculated based on data from ERA5 reanalysis, namely the 850 hPa geopotential height. Atmospheric circulation types were determined for a total of 195 grid points, including 109 located in Poland. The study presents an analysis of spatial and temporal changes in circulation conditions in the years 1950–2021 in Poland, which indicates an increase in the frequency of anticyclonic circulation in Poland since the 1980s, notably W and NW advection. The Sc, SWc and Wc types stand out among the cyclonic types with the greatest decrease in frequency across the entire territory of Poland. The anticyclonic west circulation stands out for its statistically significant increase in frequency in winter throughout the analyzed area.